LEI GERAL DE PROTEÇÃO DE DADOS: COLETA DE DADOS SENSÍVEIS DO CONSUMIDOR E A RESPONSABILIDADE CIVIL (REMUNOM, 2025)
The objective of this work is to analyze the civil liability of personal data processing agents, as stipulated by Law No. 13,709, of August 14, 2018, known as the General Law for the Protection of Personal Data (LGPD), taking into account the different contexts and interpretations of the law. In a context characterized by the information society and the data economy, driven by technological advances and the development of tools that enable the processing of large volumes of data quickly, it became necessary for Brazil to create a specific regime for the protection of personal data, thus giving rise to the LGPD. The research was based on a bibliographic review, with the aim of analyzing the different approaches to the civil liability of personal data processing agents and the implications of this liability. The conclusion reached is that, although regulated, the retention and processing of sensitive personal data is routinely used improperly and the field of civil liability is increasingly in demand, so that legal disputes are triggered to resolve conflicts related to the collection, retention and improper use, which causes inconvenience for consumers.